Factors Associated With People's Accessibility to Mental Healthcare Services in Ukraine: Focusing on Household Head Vulnerability - Min-Hee Heo; Eun-Mi Song; Hui-Won Jeon; Kyoung-Beom Kim; Jin-Won Noh (Frontiers Media S.A., 2023)
Objectives: This study examines the factors associated with access to mental healthcare services among people living in the government-controlled areas (GCAs) of Donetsk and Luhansk oblasts in Ukraine.Methods: The 2020 Ukraine Multi-Sector Needs Assessment conducted by REACH was subjected to frequency analysis, percentage analysis, and binary logistic regression to confirm the factors associated with accessibility to mental healthcare services among Ukrainian household heads.Results: Older household heads, heads with high accessibility to healthcare facilities, and those with low health expenditures were highly likely to have low access to mental healthcare services. Household heads' awareness of household members' medical assistance eligibility was significantly and positively associated with the former's mental healthcare accessibility.Conclusion: This study revealed the mental health vulnerability of people living in GCAs in Ukraine, in which the situation progresses from conflict to war. The need for mental healthcare, which is adversely affected by armed conflict, is expected to increase. Accordingly, further studies should clarify the demand for and methods to enhance mental healthcare services to ensure the timely provision of these services in the future.